Emergence of Neisseria gonorrhoeae Clone with Reduced Susceptibility to Sitafloxacin in China: An In Vitro and Genomic Study - Meiping Ye; Linxin Yao; Xinying Lu; Fangyuan Ding; Danyang Zou; Tingli Tian; Yi Lin; Zhen Ning; Jianping Jiang; Pingyu Zhou (MDPI AG, 2024)
Drug-resistant Neisseria gonorrhoeae poses an urgent threat to public health. Recently, sitafloxacin, a new-generation fluoroquinolone, has shown high in vitro activity against drug-resistant N. gonorrhoeae. However, data on its effectiveness in clinical isolates remains limited. In this study, we collected 507 N. gonorrhoeae isolates from 21 hospitals in Shanghai, China, during 2020 and 2021. Antimicrobial susceptibility testing revealed that sitafloxacin minimum inhibitory concentrations (MICs) exhibited a bimodal distribution, ranging from <0.004 to 2 mg/L. The MIC50 and MIC90 for sitafloxacin were 0.125 mg/L and 0.5 mg/L, respectively, which are 32 and 16 times lower than those for ciprofloxacin (4 mg/L and 8 mg/L, respectively). Sitafloxacin demonstrated high in vitro activity against isolates resistant to either ceftriaxone, azithromycin, or both. Notably, among the isolates with reduced sitafloxacin susceptibility (MIC ≥ MIC90), 83.7% (36/43) were identified as sequence type (ST) 8123. Further phylogenetic analysis showed that ST8123 has evolved into two subclades, designated as subclade-I and subclade-II. A majority of the isolates (80%, 36/45) within subclade-I exhibited reduced susceptibility to sitafloxacin. In contrast, all isolates from subclade-II were found to be susceptible to sitafloxacin. Subsequent genomic investigations revealed that the GyrA-S91F, D95Y, and ParC-S87N mutations, which were exclusively found in ST8123 subclade-I, might be linked to reduced sitafloxacin susceptibility. Our study reveals that sitafloxacin is a promising antibiotic for combating drug-resistant N. gonorrhoeae. However, caution is advised in the clinical application of sitafloxacin for treating N. gonorrhoeae infections due to the emergence of a clone exhibiting reduced susceptibility.